Communicating Smoke-Free Messages to Children and Women in Rural and Urban Indonesia - Sri Widati; Susy Katikana Sebayang; Ira Nurmala; Kurnia Dwi Artanti; Nur Alifia Hera; Reza Fajrinmuha; Janni Leung; Carmen Lim; Caitlin McClure-Thomas; Fitri Fausiah; Ghea Farassania (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: The increase in cigarette production use in Indonesia has contributed to the rise of non-communicable diseases, affecting both active and passive smokers. Based on the 2023 Indonesian Health Survey around 70 million people in Indonesia smoke actively, with 7.4% of them being between the ages of 10 and 18 years old. Effective tobacco control and public education communications are essential to protect vulnerable populations from the dangers of passive smoking. Objective: To increase awareness among active smokers, this study analyzed communication messages about the impact of smoking on children and women regarding communication messages as tobacco-free education. Method: This qualitative study employed Focus Group Discussions (FGDs) involving active smokers from rural and urban areas in Indonesia. Participants were recruited from urban university students living in Surabaya and rural areas of Banyuwangi through online brochures distributed at multiple universities in each region. Eligible participants were both female and male active smokers who had been smoking for the last 3 years, consumed more than five conventional cigarettes, and had used electronic cigarettes more than five times. The study included two discussion groups, each with six participants. Data analysis was using thematic analysis. Result: Six types of media communications were conducted for each child and woman. The respondents in rural East Java equally favored messages A and C. Regarding the children communication in Urban East Java, most participants preferred message C, whereas one selected message B. Regarding the women’s communication, most urban participants chose message C, with two selecting message C and one choosing message B. Most participants acknowledged the adverse health impacts of cigarette smoking on passive smokers. Both rural and urban participants selected communication messages on children’s and women’s mortality data as impactful for tobacco-free education for active smokers. Conclusion: Communication messages focusing on children and women can effectively influence the perceptions and emotions of active smokers as tobacco-free education. Media development is needed to convey educational messages that inform both active and passive smokers, encouraging awareness and behavior change.